Case report: Squamous cell carcinoma in situ of the cornea without involvement of the limbus and conjunctiva - Yun, Ji Kyu; Ryu, Young Joon; Lee, Yongwoo (Frontiers in Medicine, 2024)
Isolated corneal squamous cell carcinoma without conjunctiva and limbus involvement is rare. We report a case of isolated squamous cell carcinoma in situ of the cornea. A 67-year-old male presented with visual disturbance in the left eye (visual acuity, 0.5), with a lesion isolated to the cornea. After an initial diagnosis of keratitis, he was lost to follow-up for 15 months. He subsequently returned for re-evaluation by a corneal specialist owing to progressive visual impairment in the left eye (visual acuity, 0.2). A left scrape biopsy and histopathological examination revealed squamous cell carcinoma in situ. No systemic evaluation findings of lymphadenopathy or metastasis were observed. Following removal of the residual mass from the cornea, conjunctival tissue samples, including the limbus, were collected for histopathological examination, with negative findings. No recurrence was observed at 15 months postoperatively. Isolated corneal squamous cell carcinoma in situ can be misdiagnosed as simple corneal opacity or keratitis during clinical examination. This condition should be considered in patients with unresponsive keratitis or corneal opacities.